2008
DOI: 10.1016/j.jtcvs.2007.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Durability of mitral valve repair in Barlow disease versus fibroelastic deficiency

Abstract: When optimal surgical techniques are used, the residual recurrence rate of mitral valve regurgitation remains between 2% and 3% per year and is related to progressive degeneration of the chordae and the leaflets. Long-term results of mitral valve repair in Barlow disease are essentially the same as in fibroelastic deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 20 publications
8
126
2
1
Order By: Relevance
“…Similar results were reported by Flameng et al 29,30 In that series of 348 patients undergoing repair for degenerative mitral regurgitation, at the 10-year follow-up, survival was 80.1% and freedom from operation was 94.4%. However, freedom from 3 to 4ϩ regurgitation was only 82.2% at 5 years and 64.9% at 10 years, with a linearized recurrence rate of 3.2% per year.…”
Section: Mitral Repair Is Not a Permanent Solutionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were reported by Flameng et al 29,30 In that series of 348 patients undergoing repair for degenerative mitral regurgitation, at the 10-year follow-up, survival was 80.1% and freedom from operation was 94.4%. However, freedom from 3 to 4ϩ regurgitation was only 82.2% at 5 years and 64.9% at 10 years, with a linearized recurrence rate of 3.2% per year.…”
Section: Mitral Repair Is Not a Permanent Solutionsupporting
confidence: 86%
“…27,29 It is undeniable that the clinical practice of valve repair is globally insufficient and heterogeneous, with high-volume centers providing higher repair rates and lower operative mortality than low-volume centers. 8 Some centers report notable rates of residual or recurrent MR, 30 but in large mitral repair centers, recurrence of MR 20 and mitral reoperation rates are low, 2,20,29 between 5% and 10% at 10 years (lower than bioprostheses and equal to mechanical valves), 2 and rerepairs can be performed with good outcomes. 31 Furthermore, in large repair centers, repair rates Ն90% are achieved in most organic MR, particularly degenerative MR. 2,24,32 Whether minimally invasive mitral surgery, thoracoscopic or robotic, affects risk, discomfort, and durability of valve repair is uncertain.…”
Section: Rationale 3: Restorative Surgery Is Possible In Most Patientmentioning
confidence: 99%
“…22) Flameng, et al assessed serial echocardiographic follow-up of valve function, including the regurgitation recurrence-free rate, after plasty for Barlow's disease and FED, and reported that the etiology of myxomatous degeneration influenced the complexity of plasty techniques and postoperative valve regurgitation. 23) Especially if try to repair for BML, so called the extreme Barlow's disease showing billowing and prolapse of BL, is often difficult because it has excessive leaflet tissue characterized by myxomatous degeneration. We performed repair in an extreme Barlow's disease patient with CS for all segments, 8 CR with ePTFE sutures for AL and 2 CR for PL, resection/suture of the clear zone of PL, and a 34-mm posterior annuloplasty with autologous pericardium.…”
Section: Clinical Characteristics Of Degenerative Mitral Valve Diseasementioning
confidence: 99%
“…We share this observation of younger age in patients with a diffuse myxomatous degeneration and can support his finding of a preserved three-layer architecture of the leaflet tissue in the FED group, who are older, have more focal myxomatous changes and underwent more repair procedures than the younger patients in our myxomatous mitral valve group. Another evidence of impact of this pathological feature on surgical procedure gives Flameng [23]: he assessed echocardiographic studies including recurrence-free rate after valve repair in M. Barlow and reported an influence of etiology of myxomatous degeneration on complexity of plasty techniques [23]. An important observation from surgical view was made Adawil [24]: he gives some additional impressions to our assumption of the clinical picture consisting of older age, more recent symptoms and non myxomatous mitral valves: he found more calcific valves changes and signs of degeneration [24] and this is according to our results: we observed a more frequently valve stenosis component in this group which might give slight evidence for more annulus and perivalvular calcification.…”
Section: Discussionmentioning
confidence: 99%